Titanium alloy thin plate and method for producing the same

By employing a controlled hot and cold rolling process with intermediate annealing, the method addresses the challenge of producing titanium alloy thin plates with high Al content, achieving high strength and Young's modulus, and ensuring workability and dimensional accuracy.

JP7617453B2Active Publication Date: 2025-01-20NIPPON STEEL CORPORATION
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2022577901
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-28
Publication Date
2025-01-20
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

Existing methods struggle to produce titanium alloy thin plates with high Al content that exhibit high strength, high Young's modulus, and good workability, as conventional techniques face challenges in maintaining T-texture during hot rolling and cold rolling processes, leading to difficulties in achieving thicknesses of 2.5 mm or less.

Method used

A method involving hot rolling at specific temperatures and rolling ratios to develop T-texture, followed by controlled cold rolling with intermediate annealing, ensures the formation and maintenance of T-texture in titanium alloy thin plates, which are then subjected to temper rolling and tensile straightening to achieve desired mechanical properties.

Benefits of technology

The method enables the production of titanium alloy thin plates with high strength and Young's modulus in the sheet width direction, achieving thicknesses of 2.5 mm or less, while maintaining excellent workability and dimensional accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617453000008
    Figure 0007617453000008
  • Figure 0007617453000009
    Figure 0007617453000009
  • Figure 0007617453000010
    Figure 0007617453000010
Patent Text Reader

Abstract

 A titanium alloy thin plate according to the present invention contains specific chemical components, in which, when the crystallographic orientation of an α-phase is expressed by an Euler angle g = \{φ1,Φ,φ2\} in accordance with the Bunge notation, the maximum accumulation orientation expressed by a crystallographic orientation distribution function f(g) calculated employing an expansion index of 16 and a Gauss half-width of 5° in a texture analysis using a spherical harmonic function method for a back scattered electron diffraction method falls within the range of φ1: 0 to 30°, Φ: 60 to 90° and φ2: 0 to 60°, the degree of accumulation of the maximum accumulation orientation is 10.0 or more, the 0.2% proof stress in the width direction at 25°C is 800 MPa or more, and the Young's modulus in the width direction is 125 GPa or more, and the average thickness is 2.5 mm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to titanium alloy sheets and methods for making titanium alloy sheets. [Background technology]

[0002] Titanium is a lightweight, high-strength, and corrosion-resistant material that can be applied to the aircraft industry from the perspectives of weight reduction and fuel efficiency. Titanium alloys that meet the characteristics required for each component of an aircraft are being actively developed.

[0003] For example, Patent Document 1 discloses an α+β type titanium alloy wire containing 1.4% or more and less than 2.1% Fe, 4.4% or more and less than 5.5% Al, and the balance being titanium and impurities.

[0004] Patent Document 2 discloses an α+β type titanium alloy bar material containing 0.5% or more and less than 1.4% Fe, 4.4% or more and less than 5.5% Al, the balance being titanium and impurities.

[0005] Patent Document 3 discloses a method for manufacturing a Ti-6Al-4V alloy thin plate by pack rolling, in which one or more plate-shaped core materials are covered with a spacer material and a cover material to form a pack material, and this pack material is rolled to reduce the thickness of the core material, characterized in that the thickness of the cover material is set so that the ratio of the core material to the pack material is at least 0.25 for the initial thickness of each plate.

[0006] Patent Document 4 discloses a method for manufacturing a Ti-6Al-4V alloy thin plate by pack rolling, in which one or more plate-shaped core materials are covered with a spacer material and a cover material to form a packed material, and this packed material is rolled to reduce the thickness of the core material, characterized in that the rolling reduction ratio of the plate thickness before and after the reduction of the packed material is 3 or more, and the rolling rate per pass is 15% or more.

[0007] Patent Document 5 discloses a method for producing a titanium alloy sheet, which comprises cold rolling a hot-rolled annealed sheet of a titanium alloy consisting of, by weight, 2.5-3.5% Al, 2.0-3.0% V, the balance being Ti and ordinary impurities, in the same direction as the hot-rolling direction at a total rolling reduction of 67% or more, and then annealing the sheet at a temperature between 650 and 900°C.

[0008] Patent Document 6 discloses a method for producing an α+β type titanium alloy thin plate, which is characterized in that in the manufacturing process of an α+β type titanium alloy cold-rolled plate, intermediate annealing after cold rolling is performed under the following conditions: annealing temperature: temperature range of [β transformation point -25°C] or higher and lower than the β transformation point, annealing time: 0.5 to 4 hours, cooling rate after heating and holding: 0.5 to 5°C / sec, and temperature range for cooling at the above cooling rate: up to 300°C or lower.

[0009] Patent Document 7 discloses an α+β type titanium alloy thin plate that contains at least one fully dissolved β stabilizing element in an Mo equivalent amount of 2.0 to 4.5 mass%, at least one eutectoid β stabilizing element in an Fe equivalent amount of 0.3 to 2.0 mass%, at least one α stabilizing element in an Al equivalent amount of more than 3.0 mass% and not more than 5.5 mass%, with the balance being Ti and unavoidable impurities, and is characterized in that the average grain size of the α phase is 5.0 μm or less, the maximum grain size of the α phase is 10.0 μm or less, the average aspect ratio of the α phase is 2.0 or less, and the maximum aspect ratio of the α phase is 5.0 or less.

[0010] Patent Document 8 describes an α+β type titanium alloy hot-rolled sheet, in which (a) the normal direction of the rolling surface of the hot-rolled sheet (sheet thickness direction) is defined as ND, the hot-rolling direction is defined as RD, and the width direction of the hot-rolled sheet is defined as TD, the normal direction of the (0001) plane of the α phase is defined as the c-axis orientation, the angle that the c-axis orientation makes with ND is defined as θ, and the angle that the plane including the c-axis orientation and ND makes with the plane including ND and TD is defined as Φ, (b1) θ is 0 degrees or more and 30 degrees or less, and Φ is the angle that the entire circumference (-180 degrees to 1 (b2) among the (0002) reflection relative intensities of X-rays caused by crystal grains with θ of 80 degrees or more and less than 100 degrees and Φ of ±10 degrees, the strongest intensity is defined as XND, (b3) among the (0002) reflection relative intensities of X-rays caused by crystal grains with θ of 80 degrees or more and less than 100 degrees and Φ of ±10 degrees, the strongest intensity is defined as XTD, and (c) an α+β type titanium alloy sheet having excellent cold rollability and cold handleability is disclosed, characterized in that XTD / XND is 5.0 or more.

[0011] Patent Document 9 describes a high-strength α+β type titanium alloy hot-rolled sheet containing, by mass%, 0.8-1.5% Fe, 4.8-5.5% Al, and 0.030% or less N, and containing O and N in a range satisfying Q(%)=0.14-0.38, defined as Q(%)=[O]+2.77·[N], where [O] is the content (mass%) of O and [N] is the content (mass%) of N, with the balance being Ti and unavoidable impurities; (a) the normal direction of the hot-rolled sheet is defined as ND, the hot-rolling direction is defined as RD, and the width direction of the hot-rolled sheet is defined as TD, the normal direction of the (0001) plane of the α phase is defined as the c-axis orientation, and the c-axis orientation is defined as ND. The angle between the c-axis orientation and the plane including ND is θ, and the angle between the c-axis orientation and the plane including ND and TD is φ, (b1) θ is 0 degrees or more and 30 degrees or less, and φ is the full circumference (-180 degrees to 180 degrees), and among the relative intensities of (0002) reflection of X-rays by crystal grains with the strongest intensity, XND is the strongest intensity, (b2) θ is 80 degrees or more and less than 100 degrees, and φ is the relative intensities of (0002) reflection of X-rays by crystal grains with the strongest intensity, XTD is the strongest intensity, and (c) XTD / XND is 4.0 or more.

[0012] Patent Document 10 describes a high-strength α+β type titanium alloy cold-rolled annealed sheet containing 0.8-1.5% Fe and 0.020% or less N, with Q(%) being within a range satisfying Q=0.34-0.55, where Q(%)=[O]+2.77×[N]+0.1×[Fe], where the O content (mass%) is [O], the N content (mass%) is [N], and the Fe content (mass%) is [Fe], with the balance being Ti and unavoidable impurities. When analyzing the texture in the sheet surface direction, the normal direction to the rolling surface of the cold-rolled annealed sheet is defined as ND, the longitudinal direction is defined as RD, and the width direction is defined as TD, and the normal direction to the (0001) plane of the α phase is defined as TD. The present invention discloses an α+β type titanium alloy sheet having high strength and Young's modulus in the sheet width direction, characterized in that the ratio XTD / XND is 5.0 or more, where the direction is the c-axis orientation, the angle that the c-axis orientation makes with ND is θ, and the angle that the projection line of the c-axis orientation onto the sheet surface makes with the sheet width direction (TD) is φ, and the strongest intensity is XND among the relative intensities of (0002) reflection of X-rays by crystal grains where the angle θ is 0 degrees or more and 30 degrees or less, and φ is within the range of -180 degrees to 180 degrees, and the strongest intensity is XTD among the relative intensities of (0002) reflection of X-rays by crystal grains where the angle θ is 80 degrees or more and less than 100 degrees, and φ is within the range of ±10 degrees.

[0013] Non-Patent Document 1 discloses an α+β titanium alloy thin plate having anisotropy in strength in the rolling direction and in the direction perpendicular to the rolling direction.

[0014] Non-Patent Document 2 discloses an α+β titanium alloy thin plate that has been hot-rolled at a temperature higher than the β transformation point to reduce the anisotropy of strength in the rolling direction and in the direction perpendicular to the rolling direction. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Japanese Patent Publication No. 7-62474 [Patent Document 2] Japanese Patent Publication No. 7-70676 [Patent Document 3] Japanese Patent Publication No. 2001-300603 [Patent Document 4] Japanese Patent Publication No. 2001-300604 [Patent Document 5] Japanese Patent Publication No. 61-147864 [Patent Document 6] Japanese Patent Publication No. 1-127653 [Patent Document 7] Japanese Patent Application Publication No. 2013-227618 [Patent Document 8] International Publication No. 2012 / 115242 [Patent Document 9] International Publication No. 2012 / 115243 [Patent Document 10] International Publication No. 2015 / 156356 [Non-patent literature]

[0016] [Non-Patent Document 1] KOBE STEEL ENGINEERING REPORTS / Vol.59, No.1(2009), P.81~84 [Non-Patent Document 2] KOBE STEEL ENGINEERING REPORTS / Vol.60, No.2(2010), P.50~54 Summary of the Invention [Problem to be solved by the invention]

[0017] Incidentally, among the components of aircraft, alloys containing relatively large amounts of Al, which is a solid solution strengthening element of the α phase, such as the α+β type titanium alloy Ti-6Al-4V (64 alloy), are often used for components that require higher strength. α+β type titanium alloys such as 64 alloy, which contain a lot of Al and have high strength, are generally poor in workability and have been thought to be difficult to cold roll. On the other hand, when titanium alloys are hot-rolled in one direction at high speed at temperatures in the β region or in the α+β high-temperature region where the β phase ratio is high, a texture (T-texture) in which the c-axis of the hexagonal close-packed (hcp) structure is oriented in the sheet width direction is formed by variant selection during the transformation from β to α phase. Since the c-axis direction of titanium has a higher Young's modulus and strength than other directions, T-texture is a texture suitable for increasing strength and Young's modulus in the sheet width direction. However, when attempting to manufacture thin titanium alloy sheets by hot rolling, the temperature of the material during hot rolling drops rapidly due to the reduction in sheet thickness, and the titanium alloy in which the high-strength α phase increases and the low-temperature strength β phase decreases increases significantly in deformation resistance, which may exceed the allowable load of the rolling mill. Therefore, it is difficult to manufacture thin sheets with a thickness of 2.5 mm or less by hot rolling alone. In addition, if a recrystallization texture is formed by high-temperature annealing aimed at softening the work hardening in cold rolling, this texture easily disappears. For this reason, this texture has not been effectively utilized in thin plates with a thickness of 2.5 mm or less. For these reasons, it was previously thought to be difficult to manufacture titanium alloy thin plates with high strength and high Young's modulus that contain a large amount of Al and have a well-developed T-texture.

[0018] The present disclosure has been made in consideration of the above problems, and an object of the present disclosure is to provide an Al-containing titanium alloy thin plate having a thickness of 2.5 mm or less, which utilizes T-texture, has high strength in the plate width direction, and has a high Young's modulus in the plate width direction, and a method for manufacturing the same. [Means for solving the problem]

[0019] In the case of titanium with a hcp structure, the T-texture is expected to be deformed by slip in the hot rolling direction, so it cannot be concluded that cold rolling in the same direction is difficult. The inventors of the present invention have conducted extensive and detailed studies on the manufacture of thin plates of 2.5 mm or less by cold rolling using an Al-containing titanium alloy in which the T-texture has been developed by hot rolling.

[0020] The present disclosure has been completed based on the above findings, and the gist of the disclosure is as follows. [1] A titanium alloy thin plate according to an embodiment of the present disclosure contains, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, Ni: 0% or more and not more than 0.15%, Cr: 0% or more and not more than 0.25%, Mn: 0% or more and not more than 0.25%, C: 0% or more and not more than 0.080%, N: 0% or more and not more than 0.050%, and O: 0% or more and not more than 0.40%, with the remainder being Ti and impurities; When the crystal orientation of the α phase is expressed by Euler angles g = {φ1, Φ, φ2} according to the Bunge notation, in a texture analysis using the spherical harmonic function method of electron backscatter diffraction, the maximum accumulation orientation indicated by the crystal orientation distribution function f(g) calculated with an expansion index of 16 and a Gaussian half-width of 5° is in the range of φ1: 0 to 30°, Φ: 60 to 90°, and φ2: 0 to 60°, and the accumulation degree of the maximum accumulation orientation is 10.0 or more, 0.2% proof stress in the plate width direction at 25℃ is 800MPa or more , 1300MPa or less and The Young's modulus in the plate width direction is 125 GPa or more. The average plate thickness is 2.5 mm or less. [2] The titanium alloy thin plate according to [1] above comprises, in mass%, Fe: 0.5% or more, 2.3% or less or V: 2.5% or more, 4.5% or less may also contain [3] The titanium alloy thin plate according to the above item [2] further comprises, in mass%, replacing a part of the Fe or V, Ni: less than 0.15% Cr: less than 0.25%; and Mn: less than 0.25%. [4] In the titanium alloy thin plate described in the above [2] or [3], when the titanium alloy thin plate contains one or more elements selected from the group consisting of O, N, Fe, and V instead of a part of the Ti, Q represented by the following formula (1) may be 0.340 or less, where the O content is [O], the N content is [N], the Fe content is [Fe], and the V content is [V], in mass%. Q=[O]+(2.77×[N])+(0.1×[Fe])+(0.025×[V]) …Equation (1) [5] The titanium alloy thin plate according to any one of the above [1] to [4] has a half-width of a diffraction peak at 2θ=53.3±1° of 0.20° or more as detected by X-ray diffraction method using CuKα as a radiation source. , 1.00° or less may be also possible. [6] The titanium alloy thin plate according to any one of the above [1] to [5], having an aspect ratio of more than 3.0 and a band structure extending in the plate longitudinal direction, The area ratio of the band structure may be 70% or more. [7] The titanium alloy thin plate according to any one of the above items [1] to [6] may have a thickness dimensional precision of 5.0% or less with respect to the average thickness.

[0021] [8] A method for producing a titanium alloy thin plate according to another embodiment of the present disclosure is a method for producing a titanium alloy thin plate according to any one of the above [1] to [7], a heating step of heating a titanium material containing, by mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and 0.60% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, C: 0% or more and less than 0.08%, N: 0% or more and 0.05% or less, and O: 0% or more and 0.40% or less, with the balance being Ti and impurities; a hot rolling step of hot rolling the titanium material in one direction after the heating step; and a cold rolling step of performing one or more cold rolling passes on the titanium material after the hot rolling step in a longitudinal direction of the titanium material, The heating temperature of the titanium material in the heating step is set to T β (℃), T β ℃ or more (T β +150)℃ or less. The reduction ratio in the hot rolling step is 80.0% or more, The finishing temperature in the hot rolling process is (T β -250)℃ or more (T β -50)℃ or lower, The cold rolling step includes: The rolling ratio per cold rolling pass is 40% or less, and when multiple cold rolling passes are performed, an intermediate annealing treatment is included; The annealing conditions of the intermediate annealing treatment are as follows: The annealing temperature is 500°C or more and 750°C or less, and The annealing temperature T (° C.) and the holding time t (seconds) at the annealing temperature satisfy the following formula (2). 18000≦(T+273.15)×(Log 10 (t)+20)<22000…Formula (2) [9] In the method for producing a titanium alloy thin plate described in [8] above, after the last cold rolling pass, a final annealing may be performed at an annealing temperature of 500°C or more and 750°C or less, and satisfying the formula (2). Effect of the Invention

[0022] According to the present disclosure, it is possible to provide an Al-containing titanium alloy thin plate having a thickness of 2.5 mm or less, which utilizes T-texture, has high strength in the plate width direction, and a high Young's modulus in the plate width direction, and a method for manufacturing the same. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is an explanatory diagram for explaining the crystal orientation of α-phase crystal grains of a titanium plate using Euler angles according to Bunge's notation method. [Diagram 2] 1 is an example of a crystal orientation distribution function obtained by electron backscatter diffraction of a titanium alloy thin plate according to an embodiment of the present disclosure. [Diagram 3] 1 is an optical microscope photograph showing an example of a band structure. [Figure 4] FIG. 2 is a diagram showing an example of an optical microscope photograph of the titanium alloy thin plate according to the embodiment. [Diagram 5] FIG. 2 is a schematic diagram for explaining a method for measuring an average plate thickness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] <1. Titanium alloy thin plate> First, the titanium alloy thin plate according to the present embodiment will be described with reference to the drawings.

[0025] (1.1. Chemical composition) The chemical components contained in the titanium alloy thin plate according to this embodiment will be described. The titanium alloy thin plate according to this embodiment contains, by mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and 0.60% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, C: 0% or more and less than 0.08%, N: 0% or more and 0.05% or less, and O: 0% or more and 0.40% or less, with the balance being Ti and impurities. In the following description of the chemical components, unless otherwise specified, the notation "%" will represent "mass%".

[0026] Al is an α-phase stabilizing element and has high solid solution strengthening ability. When the Al content increases, the tensile strength at room temperature and the strength at relatively high temperatures increase. In addition, Al has the effect of increasing the Young's modulus. Furthermore, if the Al content exceeds 4.0%, the hot-rolled sheet before cold rolling can maintain high cold rolling properties. The Al content is preferably 4.5% or more. On the other hand, if the Al content exceeds 6.6%, the cold rolling properties of the hot-rolled sheet before cold rolling are significantly reduced, and Al is locally excessively concentrated due to solidification segregation, etc., and Al is ordered. The impact toughness of the titanium alloy thin sheet decreases due to this region where Al is ordered. Therefore, the Al content is 6.6% or less, preferably 6.5% or less, 6.3% or less, and more preferably 6.2% or less.

[0027] Fe is a β-phase stabilizing element. Since Fe is an element with high solid solution strengthening ability, increasing the Fe content increases the tensile strength at room temperature. In addition, since the β phase has high workability compared to the α phase, increasing the Fe content improves the workability of the titanium alloy thin plate. In order to obtain the desired tensile strength while maintaining the β phase with good workability at room temperature, the Fe content is preferably 0.5% or more. Since Fe is not essential for the titanium alloy thin plate, the lower limit of its content is 0%. The Fe content is more preferably 0.7% or more. On the other hand, since Fe is an element that is very prone to solidification segregation, when Fe is contained in excess, Fe segregates locally, and the characteristics may vary between the part where Fe is segregated and the part where it is not segregated. In addition, when Fe is contained in excess in the titanium alloy thin plate, the fatigue strength may decrease. Therefore, the Fe content is preferably 2.3% or less. The Fe content is more preferably 2.1% or less, and more preferably 2.0% or less. Fe is less expensive than β-phase stabilizing elements such as V or Si.

[0028] The Fe that may be contained in the titanium alloy thin plate according to this embodiment may be replaced with V. V is a completely dissolved β-phase stabilizing element and has a solid solution strengthening ability. In order to obtain a solid solution strengthening ability equivalent to that of Fe, the V content is preferably 2.5% or more. The V content is more preferably 3.0% or more. Since V is not essential in the titanium alloy thin plate, the lower limit of its content is 0%. Although the cost increases when Fe is replaced with V, V is less likely to segregate than Fe, so that the variation in characteristics due to segregation is suppressed. As a result, it becomes easier to obtain stable characteristics in the plate longitudinal direction and plate width direction of the titanium alloy thin plate. In order to suppress the variation in characteristics due to the segregation of V, the V content is preferably 4.5% or less. As described above, V is less likely to segregate than Fe, so that V is preferably contained in the titanium material when manufacturing a large ingot.

[0029] Although Si is a β-phase stabilizing element, it also dissolves in the α-phase and exhibits high solid-solution strengthening ability. As described above, Fe may segregate when contained in a titanium alloy thin plate at more than 2.3%, so Si may be added as necessary to increase the strength of the titanium alloy thin plate. In addition, Si has an opposite tendency to segregate to O described below, and is less likely to solidify and segregate than O. Therefore, by adding an appropriate amount of Si and O to the titanium alloy thin plate, it is expected that high fatigue strength and tensile strength can be achieved at the same time. On the other hand, if the Si content is high, an intermetallic compound of Si called silicide is formed, and the fatigue strength of the titanium alloy thin plate may decrease. If the Si content is 0.60% or less, the generation of coarse silicide is suppressed, and the decrease in fatigue strength is suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is preferably 0.50% or less, more preferably 0.40% or less, and even more preferably 0.30% or less. Since Si is not essential in the titanium alloy plate, the lower limit of the Si content is 0%, but the Si content may be, for example, 0.10% or more, or 0.15% or more.

[0030] Ni, like Fe or V, is an element that improves tensile strength and workability. However, if the Ni content is 0.15% or more, an intermetallic compound Ti2Ni, which is an equilibrium phase, is generated, and the fatigue strength and room temperature ductility of the titanium alloy thin plate may deteriorate. Therefore, the Ni content is preferably less than 0.15%. The Ni content is more preferably 0.14% or less, 0.11% or less. Since Ni is not essential in the titanium alloy plate, the lower limit of the content is 0%, but the Ni content may be, for example, 0.01% or more.

[0031] Cr is an element that improves tensile strength and workability, similar to Fe or V. However, if the Cr content is 0.25% or more, the equilibrium phase of the intermetallic compound TiCr2 is generated, and the fatigue strength and room temperature ductility of the titanium alloy thin plate may deteriorate. Therefore, the Cr content is preferably less than 0.25%. The Cr content is more preferably 0.24% or less, and even more preferably 0.21% or less. Since Cr is not essential for the titanium alloy thin plate, the lower limit of the Cr content is 0%, but the Cr content may be, for example, 0.01% or more.

[0032] Mn, like Fe or V, is an element that improves tensile strength and workability. However, if the Mn content is 0.25% or more, an equilibrium phase of intermetallic compound TiMn is generated, and the fatigue strength and room temperature ductility of the titanium alloy thin plate may deteriorate. Therefore, the Mn content is preferably less than 0.25%. The Mn content is more preferably 0.24% or less, and even more preferably 0.20% or less. Since Mn is not essential for the titanium alloy thin plate, the lower limit of the content is 0%, but the Mn content may be, for example, 0.01% or more.

[0033] Considering the effects of the above-mentioned chemical components, the titanium alloy thin plate according to this embodiment preferably contains, as an optional element, either Fe: 0.5 to 2.3% or V: 2.5 to 4.5%.

[0034] In addition, taking into consideration the effects of the above-mentioned chemical components, when the titanium alloy thin plate according to this embodiment contains either Fe: 0.5-2.3% or V: 2.5-4.5%, it is preferable to contain, in place of a portion of Fe or V, one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%.

[0035] In the case where the titanium alloy thin plate according to the present embodiment contains Fe, when it contains one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%, the total amount of Fe, Ni, Cr, and Mn is preferably 0.5% or more and 2.3% or less. When the total amount of Fe, Ni, Cr, and Mn is 0.5% or more, high tensile strength is obtained, and the β phase with good workability is maintained at room temperature, improving the workability of the titanium alloy thin plate. In addition, when the total amount of Fe, Ni, Cr, and Mn is 2.3% or less, the segregation of these elements is suppressed, and it is possible to suppress the variation in properties of the titanium alloy thin plate.

[0036] In addition, when the titanium alloy thin plate according to the present embodiment contains V, when it contains one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%, the total amount of V, Ni, Cr, and Mn is preferably 2.5% or more and 4.5% or less. When the total amount of V, Ni, Cr, and Mn is 2.5% or more, high tensile strength is obtained, and the β phase with good workability is maintained at room temperature, improving the workability of the titanium alloy thin plate. In addition, when the total amount of V, Ni, Cr, and Mn is 4.5% or less, the segregation of these elements is suppressed, and it is possible to suppress the variation in properties of the titanium alloy thin plate.

[0037] The titanium alloy thin plate according to this embodiment is preferably limited to C: less than 0.080%, N: 0.050% or less, and O: 0.40% or less. The content of each element is described below. Note that C, N, and O are not essential for the titanium alloy thin plate, so the lower limit of their content is 0%.

[0038] If a large amount of C is contained in a titanium alloy thin plate, it may reduce the ductility or workability of the titanium alloy thin plate. Therefore, the C content is preferably less than 0.080%. Note that C is an unavoidable contaminant, and the actual content is usually 0.0001% or more.

[0039] Like C, N may reduce the ductility or workability of titanium alloy thin plate if it is contained in a large amount in the titanium alloy thin plate. N is an interstitial element that penetrates into the α phase to strengthen the titanium material by solid solution, but if it is contained in a large amount, it may reduce the cold rollability. Therefore, the N content is preferably 0.050% or less. Note that N is an unavoidable mixture, and the actual content is usually 0.0001% or more.

[0040] Like C, O may reduce the ductility or workability of titanium alloy thin plate if it is contained in a large amount in the titanium alloy thin plate. Also, like N, O is an interstitial element that penetrates into the α phase to solid-solution strengthen the titanium material, but if it is contained in a large amount, it may reduce the cold rollability. Therefore, the O content is preferably 0.40% or less, more preferably 0.35% or less, and even more preferably 0.30% or less. Note that O is an unavoidable mixture, and the actual content is usually 0.0001% or more.

[0041] In the titanium alloy thin plate according to the present embodiment, when it contains one or more selected from the group consisting of O, N, Fe, and V, the Q value represented by the following formula (1) is preferably 0.340 or less, where the O content is [O], the N content is [N], the Fe content is [Fe], and the V content is [V], in mass %. The lower limit of the Q value is not particularly limited, but since O and N are inevitably mixed in, the Q value is substantially more than 0. Q=[O]+(2.77×[N])+(0.1×[Fe])+(0.025×[V]) …Formula (1)

[0042] The Q value is an index for estimating the cold rollability of titanium materials. If the Q value exceeds 0.340, the cold rollability may decrease significantly. As mentioned above, O and N decrease cold rollability when contained in large amounts. In particular, in systems containing more than 4.0 mass% Al, O and Al may order to form intermetallic compounds, decreasing cold rollability. Fe and V are β-phase stabilizing elements and basically have the effect of increasing cold rollability, but if contained in excess, the strength of the α-phase and β-phase increases, impairing ductility, and may decrease cold rollability. The coefficients of [N], [Fe], and [V] are determined taking into account their influence on the decrease in cold rollability.

[0043] The balance of the chemical composition of the titanium alloy thin plate according to this embodiment may be Ti and impurities. The impurities are, for example, H, Cl, Na, Mg, Ca, B mixed in during the refining process, and Zr, Sn, Mo, Nb, and Ta mixed in from scrap. The total amount of impurities is 0.5% or less, which is not a problem. The H content is 150 ppm or less. There is a concern that B may become coarse precipitates in the ingot. Therefore, even if it is contained as an impurity, it is preferable to suppress the B content as much as possible. In the titanium alloy plate according to this embodiment, the B content is preferably 0.01% or less.

[0044] In addition, when the titanium alloy thin plate according to this embodiment contains 0.5 to 2.3% Fe, the titanium alloy thin plate may contain an amount of V that is considered to be an impurity, and when the titanium alloy thin plate according to this embodiment contains 2.5 to 4.5% V, the titanium alloy thin plate may contain an amount of Fe that is considered to be an impurity.

[0045] In addition, it goes without saying that the titanium alloy thin plate according to this embodiment may contain various elements instead of Ti, as long as it can obtain high strength and high Young's modulus in the plate width direction. Similarly, the elements exemplified as impurities may be contained in an amount equal to or greater than the amount considered as impurities, as long as the titanium alloy thin plate has high strength and excellent workability.

[0046] As described above, the titanium alloy thin plate according to the present embodiment can have the above chemical composition. More specifically, the chemical composition of the titanium alloy thin plate according to the present embodiment can be, for example, Ti-6Al-4V, Ti-6Al-4V ELI, Ti-5Al-1Fe.

[0047] (1.2. Metal structure) Next, the metal structure of the titanium alloy thin plate according to this embodiment will be described.

[0048] [Collective tissue] First, the crystal orientation of the texture of a titanium alloy thin plate will be described. When titanium alloy is hot-rolled in one direction at high speed at a temperature in the β region or in the α+β high temperature region where the β phase ratio is high, a texture (T-texture) in which the hcp c-axis is oriented in the sheet width direction is formed due to the variant selection rule during phase transformation from β phase to α phase. T-texture is a texture formed when the unrecrystallized β phase that has been subjected to rolling deformation transforms into α phase. T-texture improves the strength and Young's modulus in the sheet width direction. When the crystal orientation of the α phase is expressed by Euler angles g={φ1, Φ, φ2} according to the Bunge notation method, if the maximum accumulation orientation indicated by the crystal orientation distribution function f(g) is in the range of φ1: 0 to 30°, Φ: 60 to 90°, and φ2: 0 to 60°, and the accumulation degree of the maximum accumulation orientation is 10.0 or more, the structure has a developed T-texture. The titanium alloy thin plate according to this embodiment has a structure in which the T-texture is developed, and contains a large amount of unrecrystallized structure.

[0049] Here, the Euler angles g={φ1, Φ, φ2} according to the Bunge notation will be described with reference to FIG. 1. FIG. 1 is an explanatory diagram for explaining the crystal orientation of the α-phase grains of a titanium alloy thin plate according to the Euler angles according to the Bunge notation. As a sample coordinate system, three coordinate axes, RD (rolling direction), TD (sheet width direction), and ND (normal direction of the rolled surface), which are mutually orthogonal, are shown. In addition, as a crystal coordinate system, three coordinate axes, X-axis, Y-axis, and Z-axis, which are mutually orthogonal, are shown. Then, each coordinate axis is arranged so that the origin of each coordinate system coincides, and a hexagonal column showing hcp is shown so that the center of the (0001) plane of hcp, which is the α-phase of titanium, coincides with the origin. In FIG. 1, the X-axis coincides with the [10-10] direction of the α-phase, the Y-axis coincides with the [-12-10] direction, and the Z-axis coincides with the

[0001] direction (C-axis direction).

[0050] In Bunge's notation, first consider a state in which the RD, TD, and ND of the sample coordinate system coincide with the X-axis, Y-axis, and Z-axis of the crystal coordinate system. From there, rotate the crystal coordinate system around the Z axis by an angle φ1, and then rotate it around the X axis (as shown in Figure 1) after the φ1 rotation by an angle Φ. Finally, rotate it around the Z axis after the Φ rotation by an angle φ2. These three angles φ1, Φ, and φ2 express a specific tilt state of the crystal or the crystal coordinate system with respect to the sample coordinate system. In other words, the crystal orientation is uniquely determined using the three angles φ1, Φ, and φ2. These three angles φ1, Φ, and φ2 are called Euler angles in Bunge's notation. The Euler angles in Bunge's notation define the crystal orientation (such as the C-axis direction) of the α-phase crystal grains of a titanium alloy thin plate.

[0051] In Fig. 1, φ1 is the angle between the intersection of the RD-TD plane (rolling plane) of the sample coordinate system and the [10-10]-[-12-10] plane of the crystal coordinate system, and the RD (rolling direction) of the sample coordinate system. Φ is the angle between the ND (normal direction of the rolling surface) of the sample coordinate system and the

[0001] direction (normal direction of the (0001) plane) of the crystal coordinate system. φ2 is the angle between the intersection of the RD-TD plane (rolling surface) of the sample coordinate system and the [10-10]-[-12-10] plane of the crystal coordinate system, and the [10-10] direction of the crystal coordinate system.

[0052] The maximum integration orientation and maximum integration degree can be determined as follows. A cross section (L cross section) perpendicular to the width direction of the titanium alloy thin plate is chemically polished at the center of the width direction (TD), and crystal orientation analysis is performed using electron backscatter diffraction (EBSD). For both the lower surface and center of the thickness of the titanium alloy thin plate, an area of ​​(total plate thickness) × 200 μm is measured in 1 μm steps in about five fields of view. The data is then analyzed using OIM Analysis by TSL Solutions. TMThe crystal orientation distribution function f(g) (ODF; Orientation Distribution Function) is calculated using software (Ver. 8.1.0). The crystal orientation distribution function f(g) is calculated in the texture analysis using the spherical harmonic function method of the EBSD method, with the expansion index set to 16 and the Gaussian half-width set to 5°. At that time, the calculation is performed so that the symmetry of the rolling deformation is taken into consideration and the calculation is made so that the thickness direction, the rolling direction, and the width direction are each line-symmetric. The ODF is a three-dimensional distribution in which the measured crystal orientation is plotted in a three-dimensional space (Euler space) of φ1-Φ-φ2, and is expressed as a distribution function. FIG. 2 is an example of the crystal orientation distribution function f(g) obtained by the electron backscatter diffraction method of the titanium alloy thin plate according to this embodiment. In FIG. 2, in order to display the Euler space in two dimensions, the Euler space is horizontally sliced ​​every 5 degrees in the angle φ2 direction, and the obtained cross sections are arranged. The maximum accumulation orientation and maximum accumulation degree can be calculated by this ODF. In Fig. 2, the maximum accumulation orientation was confirmed at φ1 = 0°, Φ = 90°, φ2 = 30° (point A), and the maximum accumulation degree was 36.3. In the above, the maximum accumulation orientation and maximum accumulation degree were obtained based on the L cross section at the center position in the width direction, but since the texture of the titanium alloy thin plate is uniform in the width direction, the maximum accumulation orientation and maximum accumulation degree may be obtained based on the L cross section at any plate width position.

[0053] [Dislocation density] In general, metal materials undergo work hardening by introducing dislocations. In titanium alloy thin plates, the higher the dislocation density, the higher the strength. The titanium alloy thin plate according to the present embodiment has a structure with a developed T-texture, and therefore contains a large amount of unrecrystallized structure. The unrecrystallized structure is a structure in which a large amount of dislocations are introduced. As a method for estimating this dislocation density, there is a method for estimating the dislocation density from the half-width of the diffraction peak obtained by X-ray diffraction (XRD; X-Ray Diffraction). The larger the half-width of the diffraction peak, the higher the dislocation density. In order to obtain sufficient work hardening, it is preferable that the half-width of the diffraction peak of the (102) plane, which appears at a position of 2θ=53.3±1° detected by X-ray diffraction using CuKα as a radiation source, is 0.20° or more. On the other hand, if the dislocation density is too high, the strength becomes too high, the notch sensitivity increases, and the plate may break. Therefore, the half width of the diffraction peak of the (102) plane is preferably 1.00° or less, and more preferably 0.80° or less.

[0054] Dislocation density is calculated by the following method. The surface of the titanium alloy thin plate is wet-polished using emery paper, and then mirror-polished using colloidal silica to obtain a mirror surface. XRD measurement is performed on the mirror-finished titanium alloy thin plate surface. XRD measurement is performed using CuKα as the radiation source, with a measurement pitch of 0.01° and a measurement speed of 2° / min, in the range of 2θ from 50.0° to 55.0°. The half-width is calculated using Rigaku's integrated powder X-ray analysis software PDXL, using X-ray diffraction data measured using Rigaku's Smartlab.

[0055] [Band organization] The titanium alloy thin plate according to the present embodiment has a band structure having an aspect ratio of more than 3.0 and extending in the plate longitudinal direction, and the area ratio of the band structure is preferably 70% or more. The band structure referred to here is, for example, a structure extending in the plate longitudinal direction as shown in the optical microscope photograph of the band structure in FIG. 3. Specifically, it refers to a crystal grain having an aspect ratio expressed by the major axis / minor axis of the crystal grain of more than 3.0. The titanium alloy thin plate according to the present embodiment has a band structure extending in the plate longitudinal direction as shown in the optical microscope photograph of the titanium alloy thin plate according to the present embodiment in FIG. 4. When the titanium alloy is hot-rolled at a temperature in the α+β region or β region, a band structure extending in the plate longitudinal direction is formed. The band structure has many grain boundaries perpendicular to the plate thickness direction. If the area ratio of the band structure is 70% or more, the propagation of a crack generated from the plate surface in the plate thickness direction can be delayed. The area ratio of the band structure is more preferably 75% or more, and even more preferably 80% or more. Furthermore, all the crystal grains may be banded structures, with the upper limit being 100.0%.

[0056] The aspect ratio and the area ratio of the band structure can be calculated as follows. A cross section (L cross section) of a titanium alloy thin plate cut perpendicular to the plate width direction at the center position in the width direction (TD) is chemically polished, and an area of ​​(total plate thickness) × 200 μm is measured in 1 μm steps at any five points of the field of view on the cross section, and crystal orientation analysis is performed using the EBSD method. From the results of this EBSD crystal orientation analysis, the aspect ratio is calculated for each crystal grain. Then, the area ratio of crystal grains with an aspect ratio of more than 3.0 is calculated. Note that, in the above, the aspect ratio and the area ratio of the band structure are calculated based on the L cross section at the center position in the width direction, but since the band structure is uniformly distributed in the width direction, the aspect ratio and the area ratio of the band structure may be calculated based on the L cross section at any plate width position.

[0057] (1.3. 0.2% proof stress in the width direction) The 0.2% proof stress in the sheet width direction at room temperature of the titanium alloy thin plate according to the present embodiment is 800 MPa or more. In the aircraft field and the like, a tensile strength close to the tensile strength at room temperature of Ti-6Al-4V, which is a general-purpose α+β type titanium alloy, is often required. If the 0.2% proof stress in the sheet width direction at room temperature of the titanium alloy thin plate is 800 MPa or more, it can be used in applications requiring high strength. The 0.2% proof stress in the sheet width direction at room temperature is preferably 850 MPa or more. On the other hand, if the strength is too high, the strength of the hot-rolled sheet before cold rolling is also high, making it difficult to cold-roll the hot-rolled sheet, and multiple passes of cold rolling may be required, resulting in increased costs. In addition, if the strength is too high, the notch sensitivity increases, and there is a possibility that the sheet may break. Therefore, the 0.2% proof stress in the sheet width direction at room temperature is preferably 1300 MPa or less. The 0.2% proof stress in the sheet width direction at room temperature is more preferably 1250 MPa or less. The 0.2% proof stress can be measured by a method conforming to JIS Z2241:2011. Specifically, the 0.2% proof stress can be measured by preparing a No. 13B tensile test piece (parallel part width 12.5 mm, gauge length 50 mm) specified in JIS Z 2241:2011 so that the tensile direction is the plate width direction of the titanium alloy thin plate, and performing a tensile test at a strain rate of 0.5% / min.

[0058] (1.4. Young's modulus in the plate width direction) The Young's modulus in the width direction of the titanium alloy thin plate according to this embodiment is 125 GPa or more. If the Young's modulus is 125 GPa or more, it can be used in applications such as the aircraft field, automobile parts, and consumer products that require high stiffness. In particular, if the Young's modulus in the width direction is 125 GPa or more, there is an advantage that the weight can be reduced by about 3 to 4% compared to the conventional case. Although there is no inconvenience if the Young's modulus is too high, the upper limit for titanium is about 150 GPa in reality. The Young's modulus in the width direction can be measured by the following method. That is, a tensile test piece No. 13B (parallel part width 12.5 mm, gauge length 50 mm) specified in JIS Z 2241:2011 is prepared so that the tensile direction is the width direction of the titanium alloy thin plate, and a strain gauge is attached to it, and loading and unloading are repeated five times at a strain rate of 10.0% / min in the stress range from 100 MPa to half of the 0.2% proof stress, and the slope is obtained, and the average value of three times excluding the maximum and minimum values ​​is taken as the Young's modulus.

[0059] (1.5. Vickers hardness HV) The Vickers hardness HV of the titanium alloy thin plate according to the present embodiment is 330 or more. The Vickers hardness HV is measured in accordance with JIS Z 2244:2009, by mirror-polishing a cross section (TD (transverse direction) surface) perpendicular to the sheet width direction at the center position in the sheet width direction (TD) of a rolled sheet, measuring the cross section at seven points under a load of 500 g and a load time of 15 seconds, and the average value of five points excluding the maximum and minimum values ​​is taken as the Vickers hardness HV. The Vickers hardness HV of the titanium alloy thin plate according to the present embodiment may be 340 or more, or 350 or more. The Vickers hardness HV of the titanium alloy thin plate according to the present embodiment may be 430 or less, or 420 or less. The Vickers hardness HV of 330 or more of the titanium alloy thin plate according to the present embodiment corresponds to a tensile strength of 1 GPa or more measured by a method according to JIS Z2241:2011. In the above, the TD surface at the center position in the longitudinal direction is used as the measurement surface for the Vickers hardness HV. However, since the variation in the Vickers hardness HV of the titanium alloy thin plate in the longitudinal direction is small, the TD surface at any longitudinal position may be used as the measurement surface for the Vickers hardness HV.

[0060] (1.6. Average plate thickness) The average thickness of the titanium alloy thin plate according to the present embodiment is 2.5 mm or less. When performing normal hot rolling, the temperature drops rapidly as the plate thickness becomes thinner, and the deformation resistance increases. As a result, when hot rolling high-strength materials, the allowable load of the rolling mill may be exceeded, making it difficult to make the average plate thickness 2.5 mm or less. On the other hand, as will be described later in detail, the titanium alloy thin plate according to the present embodiment is manufactured by a method including a cold rolling process, so that the average plate thickness can be 2.5 mm or less. In addition, although there is no particular limit to the lower limit of the average plate thickness of the titanium alloy thin plate according to the present embodiment, in the case of titanium alloys having the above strength, the average plate thickness is often 0.1 mm or more in reality. Therefore, the average plate thickness of the titanium alloy thin plate according to the present embodiment is preferably 0.1 mm or more. The average plate thickness of the titanium alloy thin plate according to the present embodiment is more preferably 0.3 mm or more.

[0061] Here, a method for measuring the average thickness will be described with reference to Fig. 5. Fig. 5 is a schematic diagram for explaining the method for measuring the average thickness. The thickness at each position, which is the center position in the width direction (TD) and at a distance of 1 / 4 of the width from each end in the width direction, is measured at five or more positions at intervals of 1 m or more in the longitudinal direction using an X-ray, a micrometer, or a vernier caliper, and the average value of the measured thicknesses is regarded as the average thickness.

[0062] (1.7. Plate thickness dimensional accuracy) The thickness dimensional accuracy of the titanium alloy thin plate according to the present embodiment is preferably 5.0% or less with respect to the average plate thickness. In pack rolling, a titanium alloy thin plate is manufactured by hot rolling a titanium material that is laminated in multiple layers and wrapped in a steel material, but since the deformation resistance of the titanium material laminated in multiple layers varies greatly depending on the temperature distribution, it is difficult to manufacture a thin plate with a uniform thickness. However, since the titanium alloy thin plate according to the present embodiment is manufactured through cold rolling as described later, it is a titanium alloy thin plate with excellent thickness dimensional accuracy. The dimensional accuracy of the titanium alloy thin plate according to the present embodiment is more preferably 4.0% or less with respect to the average plate thickness, and even more preferably 2.0% or less.

[0063] The thickness dimensional accuracy is measured by the following method. The thickness is measured at five or more locations at intervals of 1 m or more in the longitudinal direction, including the center position in the transverse direction (TD) and positions at a distance of 1 / 4 of the plate width from both ends in the transverse direction, using an X-ray, micrometer, or caliper. Using the actually measured plate thickness d and the above average plate thickness dave, the maximum value of a' calculated by the following formula (101) is taken as the thickness dimensional accuracy a. a'=(d-dave) / dave×100...Formula (101)

[0064] The titanium alloy thin plate according to the present embodiment has been described above. The titanium alloy thin plate according to the present embodiment described above may be manufactured by any method, for example, it may be manufactured by the manufacturing method of the titanium alloy thin plate described below.

[0065] <2. Manufacturing method of titanium alloy thin plate> The manufacturing method of the titanium alloy thin plate according to this embodiment includes a slab manufacturing process for manufacturing a titanium alloy slab which is a raw material (titanium material) of the titanium alloy thin plate, a heating process for heating the titanium alloy slab, a hot rolling process for hot rolling the titanium alloy slab after the heating process, a cold rolling process for cold rolling the titanium material after the hot rolling process, and, if necessary, a temper rolling / tensile straightening process for temper rolling or tensile straightening the titanium material after the cold rolling process. Each process of the manufacturing method of the titanium alloy thin plate according to this embodiment will be described below.

[0066] (2.1. Slab manufacturing process) In the slab manufacturing process, a titanium alloy slab is manufactured. As the raw material, a material having the above-mentioned chemical composition and manufactured by a known method can be used. The manufacturing method of the titanium alloy slab is not particularly limited, and for example, it can be manufactured by the following procedure. For example, an ingot is produced from sponge titanium by various melting methods such as a vacuum arc melting method, an electron beam melting method, or a hearth melting method such as a plasma melting method. Next, the obtained ingot is hot forged at a temperature in the α-phase high temperature region, the α + β two-phase region, or the β-phase single-phase region to obtain a titanium alloy slab. Note that the titanium alloy slab may be subjected to pretreatment such as cleaning treatment and cutting as necessary. In addition, when the titanium alloy slab is made into a rectangular shape that can be hot rolled by the hearth melting method, it may be subjected to hot rolling without hot forging or the like. The produced titanium alloy slab contains Al more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, Mn: 0% or more and less than 0.25%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, and O: 0% or more and less than 0.40%.

[0067] (2.2. Heating process) In this process, the titanium alloy slab is heated to the β transformation point T β ℃ or more (T β +150℃). β If the heating temperature is less than ℃, the titanium alloy slab will be rolled down when the α phase ratio is high, and the roll down when the β phase ratio is high will be insufficient. Therefore, the T-texture will not develop sufficiently. βIf the rolling temperature exceeds +150°C, there is a high possibility that the β phase will recrystallize during rolling. In this case, variant selection does not occur during the phase transformation from β to α, so T-texture is unlikely to develop. Furthermore, oxidation of the titanium alloy slab surface becomes severe, making it easier for scabs and scratches to form on the hot-rolled sheet surface after hot rolling. The temperature of the titanium alloy slab here refers to the surface temperature, which is measured with a radiation thermometer. The emissivity of the radiation thermometer is a value calibrated to match the temperature measured with a contact thermocouple for the slab immediately after it comes out of the heating furnace.

[0068] In this specification, the β transformation point T β T is the boundary temperature at which the α phase begins to form when a titanium alloy is cooled from the β phase single phase region. β can be obtained from a phase diagram. The phase diagram can be obtained, for example, by the CALPHAD (Computer Coupling of Phase Diagrams and Thermochemistry) method. Specifically, Thermo-Calc Sot Using Thermo-Calc, an integrated thermodynamic calculation system from ware AB, and a specified database (TI3), the phase diagram of titanium alloys was obtained by the CALPHAD method, and the T β can be calculated.

[0069] (2.3. Hot rolling process) When titanium alloys are hot-rolled in one direction at high speed at a temperature in the β region or the α+β region where the β phase fraction is high, the β phase transforms into α phase, forming a T-texture. βBy starting hot rolling at a temperature of (-50)°C or higher, T-texture can be sufficiently developed. Although the β transformation point differs depending on the composition of the titanium alloy slab, for example, hot rolling is started at a temperature of 950°C or higher. In order to develop T-texture, it is also important to perform rolling at a high reduction in a temperature range with a high β phase ratio, develop the texture of the β phase, and suppress recrystallization of the β phase. In order to form and develop T-texture, the manufacturing method for titanium alloy thin plate according to this embodiment includes a hot rolling process in which a titanium alloy slab is hot rolled in one direction, the reduction rate of the titanium alloy slab in the hot rolling process is 80% or more, and the finishing temperature is (T β -250)℃ or more (T β -50)°C or lower. This forms a T-texture in the titanium alloy hot-rolled sheet obtained by hot rolling the slab. The T-texture is excellent in cold rolling properties and is effective in increasing the strength and Young's modulus in the sheet width direction.

[0070] Finishing temperature (T β If the finishing temperature is less than (T -250)℃, the titanium alloy slab will be reduced when the α phase ratio is high, and the reduction when the β phase ratio is high will be insufficient. Therefore, the T-texture will not develop sufficiently. β If the temperature is lower than −250° C., the hot deformation resistance increases sharply and the hot workability decreases, so that edge cracks tend to occur and the yield rate decreases.

[0071] Finishing temperature (T β At temperatures above −50°C, the possibility of the β phase recrystallizing during hot rolling is very high. In this case, variant selection does not occur during the phase transformation from the β phase to the α phase, and the T-texture does not easily develop.

[0072] If the rolling reduction is less than 80.0%, the processing strain introduced is insufficient and the strain is not introduced uniformly throughout the sheet thickness, which may result in insufficient development of T-texture.

[0073] In order to make the texture of the titanium alloy hot-rolled sheet a strong T-texture and ensure high anisotropy, it is preferable to heat the titanium alloy slab to the above heating temperature and hold it for 30 minutes or more. By holding the titanium alloy slab at the above heating temperature for 30 minutes or more, the crystal phase of the titanium alloy slab becomes a β single phase, and the T-texture is more easily formed and developed.

[0074] The heating temperature and the finishing temperature are the surface temperatures of the titanium alloy slab and can be measured by a known method. For example, the heating temperature and the finishing temperature can be measured using a radiation thermometer.

[0075] In the hot rolling process, the titanium alloy slab can be continuously hot rolled using a known continuous hot rolling equipment. When using the continuous hot rolling equipment, the titanium alloy slab is hot rolled and then wound by a winder to become a titanium alloy hot rolled coil.

[0076] The hot-rolled titanium alloy sheet obtained through the above-mentioned hot rolling process may be annealed by a known method, pickled or cut to remove oxide scale, or may be cleaned, if necessary.

[0077] (2.4. Cold rolling process) In this process, the titanium material after the hot rolling process is subjected to one or more cold rolling passes in the longitudinal direction. The reduction ratio per cold rolling pass in the cold rolling process is 40% or less. If the reduction ratio per cold rolling pass is 40% or less, recrystallization is less likely to occur in the subsequent intermediate annealing and final annealing, and the T-texture can be maintained.

[0078] The cold rolling pass referred to here means cold rolling that is performed continuously. Specifically, the cold rolling pass refers to cold rolling from after the hot rolling process until the titanium material has a final product thickness, or from after the hot rolling process until before the temper rolling process, if a temper rolling process described later is performed after the hot rolling process. However, if intermediate annealing is performed in the cold rolling process, the cold rolling from the hot rolling process until the intermediate annealing process, and the cold rolling from the intermediate annealing process until the titanium material has a final product thickness or before the temper rolling process are each called a cold rolling pass. In addition, if intermediate annealing is performed multiple times, the cold rolling from the previous intermediate annealing process to the subsequent intermediate annealing process is also called a cold rolling pass.

[0079] The cold rolling pass temperature may be, for example, 500° C. or lower, or 400° C. or lower. There is no particular lower limit to the cold rolling pass temperature, and the cold rolling pass temperature may be, for example, room temperature or higher. Here, room temperature means 0° C. or higher.

[0080] In the cold rolling process, the titanium material after the last cold rolling pass may be subjected to a final annealing treatment. The final annealing treatment may be performed as appropriate and is not essential. The intermediate annealing treatment and the final annealing treatment are performed under the following conditions: the annealing temperature is 500°C or higher and 750°C or lower, and the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature satisfy the following formula (102). Note that (T+273.15)×(Log 10 (t)+20) is the Larson-Miller parameter. 18000≦(T+273.15)×(Log 10 (t)+20)<22000 …(102) formula

[0081] By carrying out the intermediate annealing or final annealing under the above conditions, recrystallization is suppressed and the T-texture is maintained. If the annealing temperature is less than 500°C or the annealing temperature or holding time does not satisfy the above formula (102), the recovery of the metal structure is insufficient, which causes internal cracking or edge cracking during cold rolling, and the accumulated strain may increase, causing recrystallization. On the other hand, if the annealing temperature is more than 750°C, recrystallization occurs and the T-texture is lost. In the intermediate annealing process and the final annealing process, the annealing temperature T and the annealing time t are determined so that the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature satisfy the following formula (102), and thus the T-texture is maintained and the internal cracking and edge cracking during cold rolling are suppressed.

[0082] (2.5. Temper rolling and tensile straightening process) The titanium alloy thin plate is manufactured through the above cold rolling process, and the titanium alloy thin plate after the cold rolling process is preferably subjected to temper rolling to adjust mechanical properties or tensile straightening to straighten the shape, as necessary. The rolling reduction in temper rolling is preferably 10% or less, and the elongation of the titanium alloy cold rolled plate in tensile straightening is preferably 5% or less. Note that temper rolling and tensile straightening do not have to be performed if they are not necessary. The manufacturing method of the titanium alloy thin plate according to this embodiment has been described above.

[0083] According to the manufacturing method of the titanium alloy thin plate of the present embodiment, the T-texture is generated and developed by the hot rolling process, and the titanium alloy thin plate in which the T-texture is maintained is obtained by the cold rolling process. Specifically, when the crystal orientation of the α phase is expressed by Euler angles g={φ1, Φ, φ2} according to Bunge's notation, the maximum accumulation orientation shown by the crystal orientation distribution function f(g) is in the range of φ1: 0-30°, Φ: 60-90°, φ2: 0-60°, and the accumulation degree of the maximum accumulation orientation is 10.0 or more, and a titanium alloy thin plate is obtained. This titanium alloy thin plate contains, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, Ni: 0% or more and not more than 0.15%, Cr: 0% or more and not more than 0.25%, Mn: 0% or more and not more than 0.25%, C: 0% or more and not more than 0.080%, N: 0% or more and not more than 0.050%, and O: 0% or more and not more than 0.40%. This titanium alloy thin plate has a 0.2% proof stress in the plate width direction of 800 MPa or more at 25°C and a Young's modulus in the plate width direction of 125 GPa or more.

[0084] Moreover, according to the method for producing a titanium alloy thin plate according to this embodiment, it is possible to achieve a plate thickness dimensional accuracy of 5.0% or less with respect to the average plate thickness.

[0085] In addition, according to the manufacturing method of the titanium alloy thin plate according to the present embodiment, since the rolling is performed in one direction, it is also possible to manufacture coils, and it is possible to manufacture the titanium alloy thin plate with high productivity. EXAMPLES

[0086] Hereinafter, the embodiment of the present disclosure will be specifically described with reference to examples. Note that the examples shown below are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.

[0087] Example 1 1. Manufacturing of titanium alloy thin plate First, titanium alloy ingots, which are the raw material for the titanium alloy thin plates shown in Table 1, were produced by vacuum arc remelting (VAR), and then slabs with a thickness of 150 mm, width of 800 mm, and length of 5000 mm were produced by blooming or forging. Elements other than those listed in Table 1 are Ti and impurities. "Q" in Table 1 is a value calculated by the following formula (1). Q=[O]+(2.77×[N])+(0.1×[Fe])+(0.025×[V]) …Formula (1) In the formula, [O] is the O content in mass%, [N] is the N content in mass%, [Fe] is the Fe content in mass%, and [V] is the V content in mass%.

[0088] The chemical compositions of the slabs were measured for Al, Fe, Si, Ni, Cr, Mn, and V by ICP atomic emission spectrometry. O and N were measured using an oxygen and nitrogen simultaneous analyzer, inert gas fusion, thermal conductivity, and infrared absorption spectroscopy. C was measured using a carbon and sulfur simultaneous analyzer by infrared absorption spectroscopy. The chemical compositions of each hot-rolled sheet produced were equal to the chemical compositions of the titanium alloy slabs shown in Table 1. In addition, for titanium materials A to P shown in Table 1, phase diagrams of titanium alloys were obtained by the CALPHAD method using Thermo-Calc, an integrated thermodynamic calculation system from Thermo-Calc Software AB, and a specified database (TI3), and the β transformation points T β was calculated.

[0089] [Table 1]

[0090] Next, these slabs were hot rolled under the conditions shown in Tables 2-1 and 2-3, and then hot-rolled sheet annealing, shot blasting and pickling were performed to obtain hot-rolled sheets having a thickness of 4 mm. Hot rolling was started when the temperature had dropped by about 50°C from the heating temperature. The obtained hot-rolled sheets were then cold-rolled under the conditions shown in Tables 2-2 and 2-4. In Tables 2-1 and 2-3, the "Tβ " is the β transformation point, and the "Larson-Miller parameter" is (T + 273.15) × (Log 10 (t)+20).

[0091] [Table 2-1]

[0092] [Table 2-2]

[0093] [Table 2-3]

[0094] [Table 2-4]

[0095] 2. Evaluation The titanium alloy thin plates according to the examples and comparative examples were evaluated for the following items.

[0096] 2.1. Collective organization The orientation and maximum integration degree of the titanium plates according to each of the invention examples and comparative examples were measured and calculated as follows. A cross section perpendicular to the plate width direction at the center position in the plate width direction (TD) of the titanium alloy thin plate was chemically polished, and crystal orientation analysis was performed using EBSD. An area of ​​(total plate thickness) × 200 μm was measured in about five fields of view at 1 μm intervals. The data was analyzed using OIM Analysis by TSL Solutions. TM The ODF was calculated using software (Ver. 8.1.0), and the peak position and maximum density of the density were calculated from the ODF. The ODF was calculated using texture analysis using the spherical harmonics method of the EBSD method, with the expansion index set to 16 and the Gaussian half-width set to 5°. At that time, the calculation was performed so that the symmetry of the rolling deformation was taken into account and the calculation was performed so that the thickness direction, rolling direction, and width direction were each symmetrical.

[0097] 2.2. Dislocation density Since there is a correlation between the dislocation density and the half-width of the diffraction peak detected by XRD, in this embodiment, the half-width of the diffraction peak of the (102) plane that appears at 2θ=53.3±1° detected by XRD using CuKα as a radiation source was calculated. Specifically, the surface of the titanium alloy thin plate was wet-polished using emery paper, and then the surface was mirror-polished using colloidal silica to obtain a mirror surface. XRD measurement was performed on the mirror-finished surface of the titanium alloy thin plate. The XRD measurement was performed using CuKα as a radiation source, with a measurement pitch of 0.01° and a measurement speed of 2° / min in the range of 2θ from 50.0° to 55.0°. The half-width was calculated using Rigaku's integrated powder X-ray analysis software PDXL using X-ray diffraction data measured by Rigaku's Smartlab. If the half-width is 0.20° or more, the dislocation density is at a level at which sufficient work hardening can be obtained.

[0098] 2.3. Band tissue area ratio Each sample was cut perpendicular to the width direction at the center of the sheet width and the cross section was chemically polished. Crystal orientation analysis was then performed using EBSD method on an area of ​​(total sheet thickness) x 200 μm of the cross section, covering approximately five fields of view at 1 μm intervals. The aspect ratio of each crystal grain was calculated, and the area ratio of crystal grains with an aspect ratio of more than 3.0 was calculated.

[0099] 2.4. 0.2% proof stress σT The 0.2% proof stress σT in the sheet width direction at 25°C of each titanium alloy thin plate according to the invention examples, reference examples, and comparative examples was measured in accordance with JIS Z 2241: 2011. Specifically, a tensile test piece No. 13B (parallel part width 12.5 mm, gauge length 50 mm) specified in JIS Z 2241: 2011 was prepared so that the tensile direction was the sheet width direction of the titanium alloy thin plate, and a tensile test was performed at a strain rate of 0.5% / min to measure.

[0100] 2.5. Young’s modulus E in the plate width direction The Young's modulus E in the sheet width direction of each of the titanium alloy thin plates according to the invention examples, reference examples, and comparative examples was measured by the following method. A tensile test piece No. 13B (parallel part width 12.5 mm, gauge length 50 mm) specified in Z 2241:2011 was prepared, a strain gauge was attached, and loading and unloading were repeated five times at a strain rate of 10.0% / min in the stress range from 100 MPa to half of the 0.2% yield strength, and the slope was obtained. The average value of three times excluding the maximum and minimum values ​​was taken as Young's modulus.

[0101] 2.6. Vickers hardness HV Vickers hardness HV is based on JIS Z 2244:2009 and is measured at the center of the longitudinal direction (RD) on a cross section (TD (Transverse The cross section was mirror-polished and measurements were taken at seven points with a load of 500 g for a load time of 15 seconds, and the average value of the five points excluding the maximum and minimum values ​​was taken as the Vickers hardness HV.

[0102] 2.7. Average plate thickness dave The average thickness of the titanium alloy thin plate according to each of the invention examples, reference examples, and comparative examples was measured by the following method: The thickness of each manufactured titanium alloy thin plate was measured at 5 or more positions at intervals of 1 m or more in the longitudinal direction at the center position in the width direction and at a distance of 1 / 4 of the width from each end in the width direction using X-rays or calipers, and the average of the measured thicknesses was taken as the average thickness.

[0103] 2.8. Plate thickness dimensional accuracy a The thickness dimensional accuracy of the titanium alloy thin plate according to each of the invention examples, reference examples, and comparative examples was determined by calculating the maximum value of a' using the plate thickness d actually measured by the above method and the average plate thickness dave according to the following formula (101), and the dimensional accuracy a was determined as the maximum value of a'. a'=(d-dave) / dave×100...Formula (101)

[0104] 2.9. Cold Rollability The cold rollability of the titanium alloy thin plates according to each of the invention examples, reference examples, and comparative examples was evaluated by the following method. That is, it was evaluated by the maximum edge crack after cold rolling. Then, when the maximum edge crack after cold rolling was 1 mm or less, the cold rollability was rated as very good "A", when the maximum edge crack after cold rolling was more than 1 mm and less than 2 mm, the cold rollability was rated as good "B", and when the maximum edge crack after cold rolling was more than 2 mm, the cold rollability was rated as poor "C".

[0105] 3. Results The above evaluation results are shown in Tables 3-1 and 3-2. In Table 3, "φ1", "Φ" and "φ2" are angles based on the Bunge notation method.

[0106] [Table 3-1]

[0107] [Table 3-2]

[0108] In all of the invention examples 1 to 49, the maximum accumulation orientation was in the range of φ1: 0 to 30°, Φ: 60 to 90°, and φ2: 0 to 60°, and the maximum accumulation degree was 10.0 or more. In addition, in the invention examples 1 to 26, 28 to 35, and 37 to 49, the half-width was 0.20° or more, and the area ratio of the band structure was 70% or more. In addition, in all of the invention examples 1 to 49, the 0.2% proof stress σT in the sheet width direction at 25°C was 800 MPa or more, and the Young's modulus in the sheet width direction was 125 GPa or more. The final average sheet thickness dave was 1.2 to 1.9 mm, and the dimensional accuracy a was 5.0% or less. In the comparative example 10, the Al content was low, so the 0.2% proof stress was small at 692 MPa, and the Young's modulus in the sheet width direction was small at 122 GPa. In Comparative Example 11, the Al content was high, and surface cracks and severe edge cracks occurred during hot rolling and cold rolling. In Comparative Example 12, the temperature dropped significantly in the latter half of hot rolling, and the hot-rolled sheet cracked, so a sheet with a thickness of 2.5 mm could not be produced.

[0109] Examples 1 to 6, 9 to 20, and 25 to 49 had a Q value of 0.340 or less, and these examples showed good cold rollability compared to Examples 7, 8, and 21 to 24, which had a Q value of more than 0.340.

[0110] On the other hand, in Comparative Examples 1 to 10, the manufacturing conditions were outside the manufacturing method of the titanium alloy thin plate according to the present disclosure, the maximum accumulation orientation or the accumulation degree of the maximum accumulation orientation did not satisfy the specifications of the present application, and the Young's modulus E in the plate width direction was less than 125 GPa.

[0111] Although the preferred embodiment of the present disclosure has been described in detail above, the present disclosure is not limited to such examples. It is clear that a person having ordinary knowledge in the technical field to which the present disclosure belongs can conceive of various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present disclosure.

Claims

1. In mass percent, Al: more than 4.0%, less than 6.6%, Fe: 0% or more, 2.3% or less, V: 0% or more, 4.5% or less, Si: 0% or more, 0.60% or less, Ni: 0% or more and less than 0.15% Cr: 0% or more and less than 0.25% Mn: 0% or more and less than 0.25% C: 0% or more and less than 0.080%; N: 0% or more and 0.050% or less, and O: 0% or more, 0.40% or less, with the remainder being Ti and impurities, When the crystal orientation of the α phase is expressed by Euler angles g = {φ1, Φ, φ2} according to Bunge's notation, in a texture analysis using the spherical harmonic function method of backscattered electron diffraction, the maximum accumulation orientation shown by the crystal orientation distribution function f(g) calculated with an expansion index of 16 and a Gaussian half-width of 5° is in the range of φ1: 0 to 30°, Φ: 60 to 90°, and φ2: 0 to 60°, and the accumulation degree of the maximum accumulation orientation is 10.0 or more, The 0.2% proof stress in the plate width direction at 25 ° C. is 800 MPa or more and 1300 MPa or less, The Young's modulus in the sheet width direction is 125 GPa or more, The average plate thickness is 2.5 mm or less. Titanium alloy thin plate.

2. In mass percent, The titanium alloy thin plate according to claim 1, containing Fe: 0.5% or more and 2.3% or less, or V: 2.5% or more and 4.5% or less.

3. In place of a portion of the Fe or V, Ni: less than 0.15% Cr: less than 0.25%; and The titanium alloy thin plate according to claim 2, containing one or more selected from the group consisting of: Mn: less than 0.25%.

4. In the case where one or more elements selected from the group consisting of O, N, Fe, and V are contained in place of a part of the Ti, the Q represented by the following formula (1) is 0.340 or less, when the O content is [O], the N content is [N], the Fe content is [Fe], and the V content is [V], in mass%, the titanium alloy thin plate according to claim 2 or 3. Q=[O]+(2.77×[N])+(0.1×[Fe])+(0.025×[V])…Formula (1)

5. The titanium alloy thin plate according to any one of claims 1 to 4, wherein the half-width of a diffraction peak at 2θ = 53.3 ± 1 ° detected by an X-ray diffraction method using CuKα as a radiation source is 0.20 ° or more and 1.00 ° or less.

6. The aspect ratio is greater than 3.0 and the band structure extends in the longitudinal direction of the plate. The titanium alloy thin plate according to any one of claims 1 to 5, wherein the area ratio of the band structure is 70% or more.

7. The titanium alloy thin plate according to any one of claims 1 to 6, wherein the dimensional accuracy of the plate thickness is 5.0% or less with respect to the average plate thickness.

8. A method for producing a titanium alloy thin plate according to any one of claims 1 to 7, comprising the steps of: heating a titanium material containing, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, Ni: 0% or more and not more than 0.15%, Cr: 0% or more and not more than 0.25%, Mn: 0% or more and not more than 0.25%, C: 0% or more and not more than 0.08%, N: 0% or more and not more than 0.05%, and O: 0% or more and not more than 0.40%, with the balance being Ti and impurities; a hot rolling step of hot rolling the titanium material in one direction after the heating step; and a cold rolling step of performing one or more cold rolling passes on the titanium material after the hot rolling step in a longitudinal direction of the titanium material, The heating temperature of the titanium material in the heating step is set to be equal to or higher than the β transformation point T β (℃), T β ℃ or more (T β +150) ° C. or less, The reduction ratio in the hot rolling step is 80.0% or more, The finishing temperature in the hot rolling process is (T β -250)℃ or higher (T β -50) ° C or less, The cold rolling step includes: The rolling ratio per cold rolling pass is 40% or less, and when multiple cold rolling passes are performed, an intermediate annealing treatment is included; The annealing conditions of the intermediate annealing treatment are as follows: The annealing temperature is 500° C. or more and 750° C. or less, and The annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature satisfy the following formula (2): 18000≦(T+273.15)×(Log 10 (t)+20)<22000 …Formula (2)

9. The method for producing a titanium alloy thin plate according to claim 8, wherein after the last cold rolling pass, a final annealing is performed at an annealing temperature of 500°C or more and 750°C or less, and the formula (2) is satisfied.

Citation Information

Patent Citations

  • Production of cold rolled titanium alloy plate

    JP1986147864A

  • Manufacture of alpha+beta type titanium alloy cold rolled plate

    JP1989127653A

  • Alpha+Beta type titanium alloy

    JP1995062474A

  • Alpha+Beta type titanium alloy

    JP1995070676A

  • Method of manufacturing sheet by pack rolling

    JP2001300603A